PHASE-CONTRAST IMAGING BASED ON THREE-BLOCK FRESNEL ZONE PLATE INTERFEROMETERS USING HARD X-RAY LABORATORY SOURCES - Haroutunyan, L.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The earlier represented three-block Fresnel Zone Plate interferometer based hard X-ray phase-contrast imaging setup designed for the initial plane wave radiation has been adapted to the laboratory sources of radiation. The limited distance between the source and the interferometer as well as the finite size of the source and the limited degree of monochromaticity of the illumination have been taken into account. It was shown that the decrease of the spatial coherency of the initial radiation does not worsen, and even improves the quality of the phase-contrast imaging, by suppressing the distortions caused by the X-ray diffraction at the edges of the Fresnel zone plates and the knifes of the interferometer.